Endoscopic retrograd cholongiopancreatography results in diagnosis and therapy - Fatih HİLMİOĞLU and Bülent YILDIRIM and Melih KARINCAOĞLU and Murat ALADAĞ and Vildan TAŞKIN and Bülent KANTARÇEKEN (Turkish Journal of Gastroenterology, 2019)
-